On the Limiting Distribution of the Spectra of Random Block Matrices - Alexander N. Tikhomirov (Mathematics, 2025)
The behavior of the spectra of symmetric block-type random matrices with symmetric blocks of high dimensionality is considered in this paper. Under minimal conditions regarding the distributions of matrix block elements (Lindeberg conditions), the universality of the limiting empirical distribution function of block-type random matrices is shown.